Attachment and social bonding in maximum and minimum security prison inmates - Walters, Glenn D. (American journal of criminal justice, 1991)
Attitudes towards social attachment and bonding were evaluated in groups of maximum ( N =48) and bonding were evaluated in groups of maximum ( N =46) security prison inmates and compared with the attitudes of a group of 49 noncriminal college students. Three primary styles of attachment were considered: avoidant, ambivalent/anxious, and secure. It was predicted that the maximum security condition, a group hypothesized to contain a large number of lifestyle criminals, would evidence more of an avoidant style of attachment compared to minimum security inmates or a group of college student controls. Consistent with this hypothesis, the maximum security inmates exhibited greater avoidance in their attitudes towards relationships than subjects in the other two conditions. The implications of these results are discussed.